Social Policy Towards Population Ageing: a Suggested Term Conceptualisation - Szatur-Jaworska, Barbara (Studia Oeconomica Posnaniensia, 2016)
This article proposes a conceptualisation of social policy towards population ageing and its related terms. The author distinguishes two aspects of social policy towards population ageing: adaptive and preventive policy. The author presents stipulative definitions and analyses of the following terms: social policy, the social policy agenda on population ageing, social policy agenda towards old age, and social policy agenda for old people. She also presents intensional definitions and analyses of terms, such as policy of senior citizens and active ageing policy. The author proposes a systematic view and shows relationships between these terms, concluding that they all belong to the public policy area.